Bridging the Breach: Using Positive Affectivity to Overcome Knowledge Hiding after Contract Breaches. Issue 3 (2nd April 2020) - Jahanzeb, Sadia; Clercq, Dirk De; Fatima, Tasneem
Abstract: With a basis in conservation of resources theory, this study investigates the relationship between employees' exposure to perceived contract breaches and their job performance, while also considering the mediating role of knowledge hiding and the moderating role of positive affectivity. Multisource, three-wave data from employees and their peers in Pakistani organizations reveal that breaches in the psychological contract hinder job performance, because employees respond with an unwillingness to contribute valuable knowledge to execute their job tasks. This mediating role of knowledge hiding is mitigated if employees can draw from their own positive affectivity trait. This study accordingly identifies a key factor, intentional attempts to conceal knowledge requested by other members, that can backfire and make employees suffer doubly: from unfulfilled organizational promises and from lower performance. It also reveals how this risk might be contained, that is, by encouraging employees' positive affect.